Virtual Reality Games and the Role of Body Involvement in Enhancing Positive Emotions and Decreasing Anxiety: Within-Subjects Pilot Study - Pallavicini, Federica; Pepe, Alessandro (JMIR serious games, 2020)
Background: In the last few years, the introduction of immersive technologies, especially virtual reality, into the gaming market has dramatically altered the traditional concept of video games. Given the unique features of virtual reality in terms of interaction and its ability to completely immerse the individual into the game, this technology should increase the propensity for video games to effectively elicit positive emotions and decrease negative emotions and anxiety in the players. However, to date, few studies have investigated the ability of virtual reality games to induce positive emotions, and the possible effect of this new type of video game in diminishing negative emotions and anxiety has not yet been tested. Furthermore, given the critical role of body movement in individuals’ well-being and in emotional responses to video games, it seems critical to investigate how body involvement can be exploited to modulate the psychological benefits of virtual reality games in terms of enhancing players’ positive emotions and decreasing negative emotions and anxiety. Objective: This within-subjects study aimed to explore the ability of commercial virtual reality games to induce positive emotions and diminish negative emotions and state anxiety of the players, investigating the effects of the level of body involvement requested by the game (ie, high vs low). Methods: A total of 36 young adults played a low body-involvement (ie, Fruit Ninja VR) and a high body-involvement (ie, Audioshield) video game in virtual reality. The Visual Analogue Scale (VAS) and the State-Trait Anxiety Inventory, Form-Y1 (STAI-Y1) were used to assess positive and negative emotions and state anxiety. Results: Results of the generalized linear model (GLM) for repeated-measures multivariate analysis of variance (MANOVA) revealed a statistically significant increase in the intensity of happiness (P<.001) and surprise (P=.003) and, in parallel, a significant decrease in fear (P=.01) and sadness (P<.001) reported by the users. Regarding the ability to improve anxiety in the players, the results showed a significant decrease in perceived state anxiety after game play, assessed with both the STAI-Y1 (P=.003) and the VAS-anxiety (P=.002). Finally, the results of the GLM MANOVA showed a greater efficacy of the high body-involvement game (ie, Audioshield) compared to the low body-involvement game (ie, Fruit Ninja VR), both for eliciting positive emotions (happiness, P<.001; and surprise, P=.01) and in reducing negative emotions (fear, P=.05; and sadness, P=.05) and state anxiety, as measured by the STAI-Y1 (P=.05). Conclusions: The two main principal findings of this study are as follows: (1) virtual reality video games appear to be effective tools to elicit positive emotions and to decrease negative emotions and state anxiety in individuals and (2) the level of body involvement of the virtual video game has an important effect in determining the ability of the game to improve positive emotions and decrease negative emotions and state anxiety of the players.